Profil Critical Thinking Skills Siswa SMP N 2 Karanganyar Demak - Grisselda Vania Putri; Muhammad Syaipul Hayat (Jurnal Kualita Pendidikan, 2022)
Critical thinking is an important element which students have in the school. However, the critical thinking in the students nowadays is in the lower level.  Junior high school students need to have good critical thinking skills, so that they are able to compete in the current and future era of information and globalization. The purpose of this study was to determine the profile of the critical thinking skills of junior high school students in integrated science learning (biology). The indicators used in this study from Ennis include: giving simple explanations, building basic skills, concluding, making further explanations, strategies and tactics. The subjects of this study were 32 students of Grade 9 Junior High School. This research uses a descriptive method. The data collection technique is purposive sampling. The method used is observation and tests. Data collection instruments consist of critical thinking skills instruments. The results showed that the profile of critical thinking skills of SMP N 2 Karanganyar students on average was 67.08% in the good category.